SimWars simulation case book : emergency medicine - Jacobson, Lisa; Okuda, Yasuharu; Godwin, Steven A. (Cambridge : Cambridge University Press, 2015)
The SimWars Simulation Case Book: Emergency Medicine enables novice simulation operators to quickly and effectively run simulation cases, which have been established at national SimWars events, for their respective programs and departments. The use of simulation to gain and maintain skills in healthcare has become critical to the delivery of the curricula in medical schools, nursing schools, residency programs, and hospital-based practice. Specialty boards, such as the American Board of Anesthesiology, now require simulation training as part of the Maintenance of Certification. Studies have shown that one of the main barriers to implementing simulation is the lack of trained simulation instructors and instructor time. Developed by leading emergency medicine simulation experts, this definitive collection of 46 cases includes topics intended to supplement UME and GME training, meet ACGME core competency requirements, and challenge the expert emergency physician in critical decision-making, procedural skills, ethical issues, teamwork and communication skills.
Title from publisher's bibliographic system (viewed on 13 May 2016).